Analysis of Factors Affecting Labor Productivity in Small and Medium-Sized Industries - Kimberly Febrina Kodrat (Pt. Anagata Sembagi Education, 2026)
Labor productivity remains one of the most decisive determinants of competitiveness and survival for small and medium-sized industries (SMIs), yet the factors that shape it are dispersed across a fragmented body of literature spanning manufacturing, construction, and service contexts. This article synthesizes findings from twenty-five peer-reviewed studies published between 2021 and 2026 to identify, categorize, and interpret the principal drivers of labor productivity in SMIs. Using a narrative literature review method, factors are grouped into four thematic clusters: human capital and workforce competence, capital and technology adoption, work environment and managerial practice, and institutional or policy context. The synthesis shows that human capital consistently exerts the strongest and most stable positive influence, followed by technology adoption, whose effect is conditional on firm size and absorptive capacity. Work environment and compensation factors matter most in labor-intensive small industries, while institutional support determines whether productivity gains are sustained over time. The novelty of this article lies in integrating evidence across sectors and regions into a single comparative framework rather than treating each determinant in isolation. The findings offer practical guidance for SMI owners and policymakers seeking to prioritize interventions, and they identify gaps for future empirical research, particularly on the interaction effects between human capital and digital technology in resource-constrained small industries.